FAKTOR KESULITAN GURU BIOLOGI DALAM PENERAPAN KURIKULUM MERDEKA DI SMA NEGERI 4 PALU - Nurlira Mei Widhiyanti; Yulia Windarsih; Jamhari, Mohammad (Koordinat Jurnal MIPA, 2024)
The Merdeka Curriculum is a simpler and more flexible curriculum as a result, teachers focus on important things and students become more active in responding to their interests, this study aims to identify, describe, and describe the difficulty factors for biology teachers in implementing the Merdeka Curriculum at SMA Negeri 4 Palu. This type of research used is descriptive qualitative. The results of this study indicate that the results of the Biology Teacher's Difficulty Factor Questionnaire in Implementing the Merdeka Curriculum at SMA Negeri 4 Palu are in the difficult category with the highest score found in lesson plan readiness with a percentage value of 58.3 and there is readiness for learning implementation with a percentage value of 66.7 as for evaluating learning assessment with a percentage value of 87.5. The results of biology teacher interviews related to difficulties in implementing the Merdeka Curriculum are in lesson plan readiness, readiness for learning implementation and evaluation of learning assessments